Особисте страхування: проблеми та перспективи - Голуб, Наталя Олександрівна; Holub, Natalia (Видавничий дім«Гельветика», 2024)
UA: У статті проаналізовано дискусійні питання щодо особистого страхування. Особисте страхування стає невід’ємною частиною діяльності, своєрідним механізмом підтримки економічної рівноваги. Метою роботи є виявлення сучасних проблем щодо особистого страхування та обґрунтування перспектив розвитку страхового ринку України особистого страхування. Розглянуто економічне визначення поняття «особисте страхування» та його об’єкти. Особисте страхування є однією із галузей страхування, яке дозволяє компенсувати шкоду, заподіяну здоров’ю, або отримати матеріальну компенсацію витрат в непоправних випадках. З’ясовано чинники які негативно впливають на особисте страхування. Основними з яких є недорозвиненість економіки в цілому, низький рівень довіри споживачів, обмежений доступ до фінансових послуг в регіонах, зниження рівня страхових виплат компаніями, невиконання деякими страховиками своїх зобов’язань, нестійкість національної валюти, інфляція та політична нестабільність Визначено підходи практичного та теоретичного характеру щодо вирішення із особистого страхування. /// EN: The field of personal insurance becomes an integral part of activity, a kind of mechanism for maintaining economic balance in the country and acquires strategic importance for the strengthening and development of the national economy, is an objectively necessary element of the market economy, which provides reliable protection of insured persons in the event of adverse events. Purpose to consider the concept of personal insurance and its objects in the article. Determine the factors that affect personal insurance and ways to solve them. Methods. The methodological basis of the research was based on the fundamental concepts outlined in the publications of scientists on personal insurance. Such scientific methods and techniques as analysis, synthesis, deduction and induction, system-structural method were used. Results. Personal insurance is an independent branch of insurance activity, in which the property interests of citizens related to health, life and pension provision are the objects. All types of personal insurance are important. Personal insurance is, first of all, an investment tool that has considerable popularity, in Ukraine life insurance has not yet become an effective means of developing the financial market. The main problems that hold back the development of the insurance market in Ukraine can be identified: the imperfection of the legislative framework; underdevelopment of the economy as a whole; low level of consumer confidence; financial ignorance; imperfect legislation. Conclusion. Therefore, personal insurance is an important financial instrument of the economy, which allows maintaining the achieved level of material well-being of citizens, participates in the process of formation of internal investment resources, which contributes to the solution of state social problems. The introduction of innovative approaches to the insurance business, improvement of the activity of insurance mediation and strengthening of its control, activation of the use of microinsurance opportunities for the poor (the share of which is quite significant) will also contribute to state support of socially significant types of insurance services.
Personal insurance: problems and prospects
Keywords: особисте страхування; страхування; працездатність; нещасні випадки; здоров’я; життя; personal insurance; insurance; disability; accident; health; life